INFLUENCE OF SUBSTITUTING COTTONSEED CAKE WITH RAPESEED CAKE AND MAIZE GLUTEN FEED AS PROTEIN EQUIVALENT BASIS ON GROWTH RATE, DIGESTIBILITY AND ECONOMIC BENEFITS IN SAHIWAL CALVES - M. I. Anjum; S. Javaid; M. Afzal (Journal of Animal and Plant Sciences, 2017)
The experiment was conducted to investigate the possibility of replacing cottonseed cake (CSC) with rapeseed cake (RSC) and maize gluten feed 30% (MGF) as protein equivalent basis in Sahiwal calves fed maize silage as basal diet. Twelve male calves (about 12-14 months old, and average body weight 110.5±9 kg) were randomly divided into I, II and III groups with 4 calves in each. Three iso-nutritious (CP 15% and TDN 72%) concentrates with CSC, RSC and MGF silage ad-libitum as basal diet. Results revealed non-significant difference (P>0.05) in total dry matter (DM) intake among the groups, however, daily weight gain (kg/head) by group III (0.78) was 18% and 23% higher (P<0.05) compared to group I (0.66) and II (0.63). Similarly, better feed conversion ratio was observed in group III (5.51) followed by group II (6.46) and I (6.53). The digestibility of DM, neutral detergent fibre and acid detergent fibre was alike among the groups whereas, CP digestibility and N retention was significantly (P<0.05) higher in group III compared to other groups. The economic benefits (ratio of output to input) was higher with MGF (1.29) followed by RSC (1.08) and CSC (1.00). These results suggest that MGF protein source is the best when compared with CSC or RSC on protein equivalent basis in terms of higher growth rate, nutrient digestibility and economic benefits in calves fed maize silage as basal diet.
Keywords: Sahiwal calves; Growth rate; Nutrient digestibility; Plant protein sources